Decision-Making/Simulation Games in the Social Sciences – Selected Problems - Łukasz Donaj (Facta Simonidis, 2013)
The subject matter of the publication is presenting selected forecasting problems in the social sciences. The article focuses on the method of decision-making/simulation games that, especially with the development of game theory and computers, have increasingly been used in many fields. Using examples of decision/simulation games, in particular Poznań International Model United Nations 2013/POZiMUN, the author recognises the importance of such exercises in an accurate prediction of the future.